Case report: Gastric adenosquamous carcinoma with EBV-positive component of squamous cell carcinoma mixed with gastric carcinoma with lymphoid stroma: A novel case report and literature review - Chang Lu; Jizhen Feng; Zhigang Yao; Lei Shi; Jiamei Li (Frontiers Media S.A., 2023)
Background: Gastric adenosquamous carcinoma with EBV-positive component of squamous cell carcinoma mixed with gastric carcinoma with lymphoid stroma are extremely unusual variants of gastric carcinoma. We herein reported such a case and summarized five related cases that have been reported previously.Case presentation: A 59-year-old man was admitted to our hospital with upper abdominal discomfort and acid reflux. Gastric endoscopic examination revealed an irregular ulcer in the gastric angle. Biopsy of the lesion revealed adenocarcinoma. The patient underwent laparoscopic distal gastrectomy with lymph node dissection subsequently. Histologically, the tumor showed coexistence of GASC and GCLS. SCC and GCLS were positive for EBER in situ hybridization, while adenocarcinoma component was negative. Accordingly, the present case was diagnosed as GASC with EBV-positive component of SCC mixed with GCLS.Conclusion: GASC with EBV-positive component of SCC mixed with GCLS is extremely rare. Although the pathogenesis of GASC and the role of EBV in the development of an ASC component have not been fully elucidated, this case will help clinicians and pathologists better understand this special subtype of gastric tumor.